Mitochondrial Lon-induced mitophagy benefits hypoxic resistance via Ca2+-dependent FUNDC1 phosphorylation at the ER-mitochondria interface - Ananth Ponneri Babuharisankar; Cheng-Liang Kuo; Han-Yu Chou; Vidhya Tangeda; Chi-Chen Fan; Chung-Hsing Chen; Yung-Hsi Kao; Alan Yueh-Luen Lee (Cell Death and Disease, 2023)
Abstract During hypoxia, FUNDC1 acts as a mitophagy receptor and accumulates at the ER (endoplasmic reticulum)-mitochondria contact sites (EMC), also called mitochondria-associated membranes (MAM). In mitophagy, the ULK1 complex phosphorylates FUNDC1(S17) at the EMC site. However, how mitochondria sense the stress and send the signal from the inside to the outside of mitochondria to trigger mitophagy is still unclear. Mitochondrial Lon was reported to be localized at the EMC under stress although the function remained unknown. In this study, we explored the mechanism of how mitochondrial sensors of hypoxia trigger and stabilize the FUNDC1-ULK1 complex by Lon in the EMC for cell survival and cancer progression. We demonstrated that Lon is accumulated in the EMC and associated with FUNDC1-ULK1 complex to induce mitophagy via chaperone activity under hypoxia. Intriguingly, we found that Lon-induced mitophagy is through binding with mitochondrial Na+/Ca2+ exchanger (NCLX) to promote FUNDC1-ULK1-mediated mitophagy at the EMC site in vitro and in vivo. Accordingly, our findings highlight a novel mechanism responsible for mitophagy initiation under hypoxia by chaperone Lon in mitochondria through the interaction with FUNDC1-ULK1 complex at the EMC site. These findings provide a direct correlation between Lon and mitophagy on cell survival and cancer progression.